NPPF and Archaeology: A Discussion - Rob Lennox (Papers from the Institute of Archaeology, 2013)
Flatman and Perring have demonstrated in this article that the NPPF has thus far engendered mixed emotions for those of us working in the historic environment sector, but they seem to suggest that the overriding sense is one of relief after a fearful consultation process; the stormy waters have died down and it looks like steady sailing ahead. However, perhaps the real problem lies in the fact that the promising winds of change have dropped too, and that our ship may be in danger of being becalmed.
Keywords: National Planning Policy Framework; planning; development